Effects of PGPB Inoculations on Plant Growth and Quality of Spray Carnation Cultivation in Greenhouse - Esra Yıldız Taşkesen; Nalan Türkoğlu; Arzu Çığ (Journal of Agricultural Sciences)
In order to achieve the desired quality characteristics and good growth in ornamental plants, various applications are carried out. Recently, the importance of beneficial bacteria, which play an extremely important role in sustainable ecology and are environmentally friendly, has been increasingly recognized. However, the effect of beneficial bacteria, which are not sufficiently applied in ornamental plants as well as in other plant groups, on the growth and quality characteristics of spray carnation variety, which is the most preferred among cut flowers, was investigated in this study. In the greenhouse, the carnation seedlings were treated with Enterobacter ludwigii (KF29A), Pseudomonas fluorescens (KF31B), Paenarthrobacter nitroguaiacolicus (KF3B), Pseudomonas sp. strain VG242B (KF5A), Paenibacillus xylanilyticus (KF63C), Pseudoalteromonas tetraodonis (TV126C) bacteria which have been selected according to nitrogen fixation, phosphate solubilizing, ACC deaminase and siderophore production properties were applied. In the study, in which phenological and morphological observations were made, the effects of bacterial inoculations were tried to be determined. The effects of beneficial bacteria treatments on the number of petals, the number of nodes, the length between the nodes and the weight of the branches in the carnation plant were statistically insignificant; effects on the parameters of bud first bloom time, full bloom time, time from planting to first harvest, number of flower buds and stem length (P<0.01), flower (diameter) width and stem thickness (P<0.05) was found to be statistically significant. First bud bloom, full bloom and time from planting to first harvest are 103.38 days, 103.74 days and 106.28 days (KF63C) respectively, maximum number of flower buds is 4.77 (TV126C), flower diameter is 46.73 mm at the widest (KF63C), the highest stem thickness was 3.39 cm (KF3B) and the highest stem length was 56.33 cm (TV126C). The first flowering time of the buds appeared with a delay of approximately 10-30 days compared to the control with bacterial applications. It is seen that bacterial applications cause an increase on flower stem thickness, flower stem length, flower bud and petal number.